2012
DOI: 10.1111/j.1651-2227.2012.02684.x
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3 essential fatty acid status is improved during nutritional rehabilitation of adolescent girls with eating disorders and weight loss

Abstract: Adequate nutrition, normalization of eating behaviours, weight gain and the consequent return to normalization of metabolism and endocrine function are sufficient to ensure normalization of essential fatty acid status. Supplementation with omega-3 polyunsaturated fatty acids does not appear warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
3
20
1
Order By: Relevance
“…For n-6 PUFAs, we did not identify any significant differences in LA or ARA, but DGLA and OBA were both elevated in AN compared to controls [15]. Langan et al [21], Zak et al [23], and Swenne et al [24] found LA to be lower in AN, whereas Swenne et al [26] and Caspar-Bauguil et al [27] identified decreased ARA in erythrocyte membrane and RBC phospholipid of AN, respectively.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…For n-6 PUFAs, we did not identify any significant differences in LA or ARA, but DGLA and OBA were both elevated in AN compared to controls [15]. Langan et al [21], Zak et al [23], and Swenne et al [24] found LA to be lower in AN, whereas Swenne et al [26] and Caspar-Bauguil et al [27] identified decreased ARA in erythrocyte membrane and RBC phospholipid of AN, respectively.…”
Section: Discussionmentioning
confidence: 78%
“…In 2011 and 2012, Swenne et al published 3 related papers [2426] examining non-fasting plasma phospholipid and erythrocyte membranes (ERY) PUFAs in up to 220 girls with eating disorders and 39 healthy controls [24,25]. The authors also examined changes of ERY PUFAs in 24 ED who had PUFA measured at admission and the 1-year follow-up visit [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This Ethyl eicosapentaenoic acid (E-EPA, an omega-3 fatty acid) has been suggested as a treatment for anorexia nervosa (Ayton, et al, 2004). Swenne and Rosling (2012) recently reported that rehabilitated anorexic girls exhibited normal fatty acid profiles.…”
Section: Fatty Acid Profile and Membrane Fluiditymentioning
confidence: 99%